Fiber and phenolic compounds contribution to the hepatoprotective effects of mango diets in rats fed high cholesterol/sodium cholate - Ruiz-Canizalez, Jaqueline (2019)
The present study evaluated the contribution of mango fiber (MF) and mango phenolic compounds (MP) to the hepatoprotective effect of freeze‐dried mango pulp (FDM) cultivar (cv.) “Ataulfo” diets in high cholesterol/sodium cholate (HCC)–fed rats. Male Wistar rats were fed with a HCC diet for 12 weeks, either untreated, or supplemented with MF, MP, FDM, or a control diet (no HCC; n = 6/group). All mango treatments significantly decreased hepatic cholesterol deposition and altered its fatty acid profile, whereas MF and MP mitigated adipose tissue hypertrophy. MF caused a lower level of proinflammatory cytokines (IL‐1α/β, IFN‐γ, TNF‐α) whereas FDM increased the anti‐inflammatory ones (IL‐4, 6, 10). Mango treatments increased catalase (CAT) activity and its mRNA expression; superoxide dismutase (SOD) activity was normalized by MF and FDM, but its activity was unrelated to its hepatic mRNA expression. Changes in CAT and SOD mRNA expression were unrelated to altered Nrf2 mRNA expression. Higher hepatic PPARα and LXRα mRNA levels were found in MP and MF. We concluded that MF and MP are highly bioactive, according to the documented hepatoprotection in HCC‐fed rats; their mechanism of action appears to be related to modulating cholesterol and fatty acid metabolism as well as to stimulating the endogenous antioxidant system